Aspidistra guizhouensis (Asparagaceae), a new species from Guizhou, China - Liu, Anli; He, Shunzhi; Xu, Wenfen (Phytotaxa, 2015)
Aspidistra guizhouensis S.Z.He & W.F.Xu, a new species of Aspidistra from Guizhou province, China, is described, illustrated and a line drawing of the species is provided. Aspidistra guizhouensis is similar to the widespread species Aspidistra retusa K.Y.Lang & S.Z.Huang and Aspidistra sichuanensis K.Y.Lang & Z.Y.Zhu. The karyotype of this species is analysed.